Association of personality, work values and socio-cultural factors with intrapreneurial orientation - Sihna, Nupur; Srivastava, Kailash B.L. (New Dehli : Sage, 2013)
This study reports on the impact of some personality factors, work values and socio-cultural factors on intrapreneurial orientation. Data were collected from 272 executives working in the manufacturing sector. Correlation and multiple regression statistics were performed to test the strength of association among measures of intrapreneurial orientation, big-five locator personality, eight work-values and four socio-cultural factors. Results showed that neuroticism significantly but negatively, and extraversion, altruism, creativity management and achievement positively predicted intrapreneurial orientation. Socio-cultural factors had significantly interacted with personality factors, but its impact on the association of work values with intrapreneurial orientation remained almost unchanged. The HR professionals can utilise this information in fostering facilitative climates for innovations in their organisations.
Keywords: Association of personality; Work values and socio-cultural factors